A novel theory on the predictive value of variation in the β-endorphin system on the risk and severity of PTSD. Issue 3 (3rd May 2020) - Mac Gillavry, David William; Ullrich, David
ABSTRACT: Despite growing interest in genetic and psychosocial indicators of heightened susceptibility to posttraumatic stress disorder (PTSD), a predictive model, which explains why some individuals develop PTSD in response to life-threatening traumatic events, while others, when faced with the same or similar experiences, do not, has thus far remained out of reach. In this paper, we review the literature on gene–environment interactions in β-endorphin system functioning with regard to PTSD and suggest that variation, both genetic and with regard to environmental stimuli, in systems which, like the β-endorphin system, distort human perception of life-threatening traumatic experiences may account for some of the variance in resilience to the disorder. Given the role of β-endorphin in both social connections and physical exercise, this becomes especially relevant with regard to military selection, training, and leadership processes.